Pengenalan Computational Thinking untuk Guru-guru di Kabupaten Purwakarta - Rizki Hikmawan; Dian Permata Sari; Suprih Widodo; Dimas Setiawan; Muhammad Irwan Ramadhan; Sadam Fauzi (Jurnal Pengabdian Pada Masyarakat, 2021)
COMPUTATIONAL THINKING INTRODUCTION FOR TEACHERS IN PURWAKARTA. The changing needs of the industrial world must always be responded quickly by the world of education. The needs of the industrial world change along with technological developments. Currently, the industry has entered the 4.0 era or better known as the digital industry. Today’s society only views computers only as tools, not as a science to educate, even negative when viewed from media notifications that report many cases of technology abuse. This causes parents to tend to limit their children’s use of technology. If children who incidentally are the future of the nation are limited or even prohibited from using technology, of course Indonesia will not be able to compete in the digital era of industry. This mindset must be straightened out, that the computer is not only a tool but also a benchmark for thinking patterns. Community service activities will take place in Purwakarta district in the form of counseling and learning Computational Thinking. Beginning with a face-to-face seminar with lecture learning methods, and questions and answers. After the teachers received counseling, then we facilitated their students to test their computational thinking skills through the Bebras Challenge, in collaboration with the NBO Bebras Indonesia.